2014
DOI: 10.1007/s10514-014-9389-9
|View full text |Cite
|
Sign up to set email alerts
|

Human-inspired force compliant grasping primitives

Abstract: We address the problem of grasping everyday objects that are small relative to an anthropomorphic hand, such as pens, screwdrivers, cellphones, and hammers from their natural poses on a support surface, e.g., a table top. In such conditions, state of the art grasp generation techniques fail to provide robust, achievable solutions due to either ignoring or trying to avoid contact with the support surface. In contrast, when people grasp small objects, they often make use of substantial contact with the support s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Each of the strategies was tailored to exploit constraints commonly present in real-world grasping problems. Similarly in [2], Kazemi et al reported the results of human subjects grasping studies which show the extent and characteristics of the contact with the environment under different task conditions. A closed-loop hybrid grasping controller that mimics this interactive, contact-rich strategy was also tested using a a compliant 7-DoFs Barrett Whole-Arm Manipulator (WAM).…”
Section: Introductionmentioning
confidence: 95%
“…Each of the strategies was tailored to exploit constraints commonly present in real-world grasping problems. Similarly in [2], Kazemi et al reported the results of human subjects grasping studies which show the extent and characteristics of the contact with the environment under different task conditions. A closed-loop hybrid grasping controller that mimics this interactive, contact-rich strategy was also tested using a a compliant 7-DoFs Barrett Whole-Arm Manipulator (WAM).…”
Section: Introductionmentioning
confidence: 95%
“…Also recently, both grasp planning algorithms and grasping mechanisms have begun to take advantage of EC [13], albeit not systematically. While sequences of EC exploitation primitives have been shown to be robust and capable [9], [26], there has been no comprehensive research on how to enumerate and describe these primitives or how to sequence them into task-directed manipulation plans.…”
Section: Traditional Grasp Plannersmentioning
confidence: 99%
“…Recently, researchers have shown interest in studying in-contact skills. In-contact tasks which have been learned from demonstration include cleaning a vertical surface [2], controlling stiffness [3], ball-in-box [4], pouring drink [4], box pulling [5], flipping task [5], stapling [6], and grasping small objects [7]. However, all these studies aim at learning a policy merely to reproduce the demonstrated force.…”
Section: Reinforcement Learning For Improving Imitated In-contact Skillsmentioning
confidence: 99%